Yield Gap Analysis of Toria (Brassica campestris) through Front Line Demonstrations in Kandhamal District of Odisha - D. V. Singh , S. K. Mukhi; M. R. Mohapatra (Indian Journal of Extension Education, 2016)
The present study was carried out at Krishi Vigyan Kendra, Kandhamal to know the yield gaps between improved package and practices (IP) under Front Line Demonstration (FLD) and farmer’s practice (FP) of toria crop. Yield attributes of both demonstration and farmers’ practice were recorded and their yield gap, technology gap, extension gap and technology index were analyzed. The average five years data revealed that an average yield of demonstrated plot was obtained 10.01 q/ha over local check (6.55 q/ha.) and there is an increase in average productivity by 52.97 per cent. On an average technology gap was recorded to be 1.99 q/ha. While average extension gap was observed to be 3.46 q/ha. Average technology index was recorded as 16.63 per cent. The average cost benefit ratio was 2.55 under demonstration, while it was 1.75 under control plots. The trend of technology gap reflected the farmer’s cooperation in carrying out demonstrations with encouraging results in subsequent years. By conducting front line demonstration of proven technologies, yield potential of rapeseed-mustard crop could be enhanced with increase in the income level of the farming community.